Kinetic modeling of hemicellulose-derived biomass hydrolysis under high pressure CO2–H2O mixture technology - Relvas, F. (2016)
This work is focused on the development of kinetic models of hydrolysis of hemicellulose-derived wheat straw under high-pressure CO2.H2O technology. The experiments were performed at fixed temperature (180.C), varying pressure from 0 (water-only reaction), 20, 35 to 50 bar of initial CO2 pressure and reaction times varied from 0 to 45 min. The three accurate kinetic models allowed to describe the effect of reaction conditions mainly hitherto not studied CO2 pressure and reaction time on the concentration of intermediate compounds such as xylose and arabinose in both oligomer and monomer form as well as final compounds e.g. acetic acid, furfural and other degradation products. Modeling demonstrated that addition of CO2 plays an important role in kinetics study of hemicellulose fraction hydrolysis being the fastest step the polysaccharides f hydrolysis into sugars in oligomer form. Even negligible amount of CO2 (20 bar of initial pressure) improves the initial kinetic constant of aforementioned reaction by almost 40% in comparison to water-only process. Depletion of oligosaccharides ' concentration and counterbalanced production of monomer sugars were found for longer reaction times, achieving maximum faster for CO2 assisted than CO2 free processes. Moreover, the increase of initial CO2 pressure demonstrated to be highly efficient in enhancement of the kinetic constants of all reactions occurring in the liquors. The developed models demonstrated a good fitting to the experimental data albeit the complex composition of raw material as well as the multistep analytical process.